Processing Tofu Liquid Waste into Liquid Organic Fertilizer With the Addition of Lamtoro Leaves as an Effort Prevention of Environmental Pollution - Mualim; Ganefati, Sri Puji; Jubaidi; Marwanto, Andriana; Rahmawati, Ullya (BRIN Publishing (Penerbit BRIN), 2025)
Adding lamtoro leaves (Leucaena leucocephala) in the wastewater treatment of tofu into liquid organic fertilizer (LOF) is one of the efforts to protect the environment. This study investigated the effect of adding lamtoro leaves on the nutrient content, specifically nitrogen, phosphorus, potassium (NPK), and carbon, of LOF derived from tofu industry waste in Bengkulu, Indonesia. Tofu wastewater contains high levels of BOD, COD, and gases such as oxygen (O₂), hydrogen sulfide (H₂S), carbon dioxide (CO₂), and ammonia (NH₃), exceeding environmental quality standards. Lamtoro leaves contain 3.84% nitrogen, 0.2% phosphorus, 2.06% potassium, 24.7% protein, and 53.71% carbohydrates, making them a promising additive to enhance LOF's NPK and carbon content. This study employed a quasi-experimental design using a pre-post and control group format. Data were statistically analyzed using the Kruskal-Wallis test. The statistical analysis showed that the addition of lamtoro leaves significantly increased the levels of nitrogen (α = 0.049), potassium (α = 0.044), and carbon (α = 0.019). At the same time, the change in phosphorus content was not statistically significant (α = 0.136). These findings indicate that incorporating lamtoro leaves improves soil nutrients and provides natural plant nutrition, enhancing soil quality and carrying capacity, contributing to ecosystem protection, environmental pollution prevention, and public health improvement.